OPTIMALIZATION OF HOSPITAL EMPLOYEE PERFORMANCE dr. REKSODIWIRYO PADANG - Jaya Subrata, I Nyoman; Rizky, M. Chaerul (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
This research was conducted in order to see Optimizing Employee Performance at Dr Reksodiwiryo Hospital Padang. With this research the researchers conducted this research on Jl. Dr. Wahidin No.1, Ganting Parak Gadang, Padang Timur District, Padang City, West Sumatra 25132. This research uses quantitative research, and uses primary data sources, the population of this research is 75 employees and the sample used is the entire population, so it uses a sampling technique bored for research, data collection used the questionnaire distribution method and used the Phat analysis model as the research model and used the Smart PLS version 3 tool to calculate research results. The results of this research are as follows: Leadership has a positive and insignificant effect on employee performance with an original sample value of 0.059 and a p value of 0.725. Work Quality has a positive and insignificant effect on Employee Retention with an original sample value of 0.123 and a p value of 0.538. Work Quality has a positive and insignificant effect on employee performance with an original sample value of 0.126 and a p value of 0.289. Employee retention has a positive and significant effect on employee performance with a value of 0.783 and a p value of 0.000. Leadership has a positive and significant effect on employee retention with an original sample value of 0.841 and a p value of 0.000. Leadership influences employee performance through employee retention positively and significantly with an original sample value of 0.658 and a p value of 0.000. Work Quality has an indirect and insignificant effect on Employee Performance through Employee Retention, with an original sample value of 0.096 and a p value of 0.540.